2008
DOI: 10.1124/mol.107.036384
|View full text |Cite
|
Sign up to set email alerts
|

3-Methylcholanthrene Displays Dual Effects on Estrogen Receptor (ER) α and ERβ Signaling in a Cell-Type Specific Fashion

Abstract: The biological effects of 17␤-estradiol (E 2 ) are mediated by the two estrogen receptor (ER) isoforms ER␣ and ER␤. These receptors are ligand-inducible transcription factors that belong to the nuclear receptor superfamily. These receptors are also targets for a broad range of natural and synthetic compounds that induce ER activity, including dietary compounds, pharmaceuticals, and various types of environmental pollutants such as bisphenols and polychlorinated hydroxy-biphenyls. Here, we study the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…Our results showing very little parent compound in the media 12 h after MC treatment lends further credence to this idea and were consistent with the studies of Swedenborg et al (2008). Thus, our findings indicate that the induction of CYP1A1 by MC at 72 h and beyond was independent of the presence of the parent compound, as we reported previously in the in vivo rat model (Moorthy, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Our results showing very little parent compound in the media 12 h after MC treatment lends further credence to this idea and were consistent with the studies of Swedenborg et al (2008). Thus, our findings indicate that the induction of CYP1A1 by MC at 72 h and beyond was independent of the presence of the parent compound, as we reported previously in the in vivo rat model (Moorthy, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…A later study demonstrated that the ability of 3-MC to activate ERa-dependent transcription requires biotransformation to metabolites with estrogenic activity. Interestingly, in cells where 3-MC was not metabolized, 3-MC acted as an antiestrogen in close analogy to dioxin (Swedenborg et al 2008). Similar findings have been obtained with other AhR ligands such as BaP (Arcaro et al 1999).…”
Section: Interference With Co-activator Recruitmentsupporting
confidence: 71%
“…HAHs and PAHs are potent ligands of the aryl hydrocarbon receptor (AhR), one of the main receptors mediating the response to xenobiotics. Even though HAHs and PAHs do not bind hormone receptors as such, some of them (e.g., B[a]P and 3-MC) are metabolized into compounds that are potent ER activators [11,12].…”
Section: Man-made Chemicalsmentioning
confidence: 99%